2024
DOI: 10.1161/atvbaha.123.320144
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Factor and COVID-19 Associated Thrombosis

Nigel Mackman

Abstract: Microbial infections activate the innate and adaptive immune systems. 1 Pathogen-associated molecular patterns produced by microbes, such as double-stranded RNA, are detected by PRRs (pattern-recognition receptors), such as toll-like receptor 3, and this leads to the expression of interferons and cytokines. 1 , 2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
(76 reference statements)
0
1
0
Order By: Relevance
“…Several studies have found that circulating TF is increased in patients with COVID-19, but the mechanisms underlying this upregulation and how it contributes to COVID-19 clinical manifestations remains unknown. [10][11][12][13] Because of the associations between inflammation and thrombosis in COVID-19, we hypothesized that activated monocytes themselves could orchestrate both inflammation and thrombosis associated with SARS-CoV-2 infections. In this study, we used systems biology approaches, including targeted proteomics, transcriptomics, and mass cytometry (cytometry by time of flight [CyTOF]), to define circulating inflammatory/vascular mediators and the immune phenotypes of circulating immune cells from subjects with COVID-19.…”
mentioning
confidence: 99%
“…Several studies have found that circulating TF is increased in patients with COVID-19, but the mechanisms underlying this upregulation and how it contributes to COVID-19 clinical manifestations remains unknown. [10][11][12][13] Because of the associations between inflammation and thrombosis in COVID-19, we hypothesized that activated monocytes themselves could orchestrate both inflammation and thrombosis associated with SARS-CoV-2 infections. In this study, we used systems biology approaches, including targeted proteomics, transcriptomics, and mass cytometry (cytometry by time of flight [CyTOF]), to define circulating inflammatory/vascular mediators and the immune phenotypes of circulating immune cells from subjects with COVID-19.…”
mentioning
confidence: 99%